Soil and nutrition interactions - Mattos Jr., Dirceu; Kadyampakeni, Davie M.; Quinones, Ana; Boaretto, Rodrigo Marcelli; Morgan, Kelly T.; Quaggio, Jose A. (Elsevier, 2021)
Citrus production is largely regulated by the availability of nutrients in the soil, which is affected by its physical, chemical, and biological characteristics. Soils under citrus cultivation vary in the major producing regions of the world from the subtropical to the tropical and Mediterranean-type areas. Understanding soil-plant relationships is important for the establishment of better management practices to increase production efficiency and fruit quality. To this end, tools are available to determine soil fertility and the nutritional status of citrus through soil and leaf analyses; the obtained information is associated with plant responses to nutrient supply and environmental conditions, allowing detailed recommendations for the optimal management of nutrients in citrus orchards. Thus, this chapter describes the main soil orders based on the world taxonomy system, the role of mineral nutrients in the production and quality of citrus, soil and plant monitoring, as well as the main management strategies of orchards based on the application of fertilizers in dry granular form, via fertigation, and through foliar application. This provides a basis to improve sustainability of global citrus production.